2013
DOI: 10.5455/2320-1770.ijrcog20130922
|View full text |Cite
|
Sign up to set email alerts
|

A study of morbidity and drug utilization pattern in indoor patients of high risk pregnancy at tertiary care hospital

Abstract: Background: Pregnancy represents a special physiological state during which the use of drug is of growing concern due to risk of teratogenicity. High risk pregnancy is common threat to mother and foetus. Therefore, our aim was to study the drug utilization and morbidity pattern in high risk pregnancy in hospitalized pregnant women. Methods: An observational, prospective study was carried out in 250 patients for 6 months in the tertiary care hospital. Protocol was approved by the Institutional Review Board (IRB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 27 publications
1
9
0
Order By: Relevance
“…Our results are in accordance with previous Indian studies though some other studies report lower use of iron and folic acid during pregnancy. 8,14,17,18 The use of other drugs such as antihypertensive drugs, gastrointestinal drugs, uterine relaxants, antiepileptic drugs, hormones were largely problem oriented (Table 2) and is in accordance with earlier studies. 14 …”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…Our results are in accordance with previous Indian studies though some other studies report lower use of iron and folic acid during pregnancy. 8,14,17,18 The use of other drugs such as antihypertensive drugs, gastrointestinal drugs, uterine relaxants, antiepileptic drugs, hormones were largely problem oriented (Table 2) and is in accordance with earlier studies. 14 …”
Section: Discussionsupporting
confidence: 76%
“…Similar results have been reported by previous studies. 14 Most of the women attending this hospital come from lower socioeconomic class. High prevalence of poor nutritional status, vitamin and mineral deficiencies in this class warrants prophylactic use of vitamins and minerals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These drugs were the least utilized from FDA pregnancy risk category drugs which was in line with that of the study conducted in Brazil (1.85%) [28] and in Coastal town, India (3.13%) [33] where medications used for pregnant women were from this category. A study conducted in Addis Ababa [34] had a higher value than this finding whereas a study conducted in Ahmedabad, India revealed that there was no drug used from this category [35]. In category D, there is positive evidence of human fetal risk based on adverse reaction data from investigational or marketing experience or studies in humans, but potential benefits may warrant use of these drug in pregnant women despite potential risks [21].…”
Section: Discussionmentioning
confidence: 99%
“…High prevalence of poor nutritional status, vitamin and mineral deficiencies in this class warrants prophylactic use of vitamins and minerals. 10 Accordingly most commonly used medications (in 100% of women) in the present study were iron, folic acid, calcium and multivitamin B complex (Table 5). Our results are in accordance with previous Indian studies.…”
Section: Discussionmentioning
confidence: 71%